Latin America and China: What Next for China–Latin American Strategic Relationship?. (1st May 2017) - Francisco Dominguez
Abstract : The long neoliberal night that descended on Latin America since the military coup against Salvador Allende in Chile in 1973, began to be reversed with the arrival of Hugo Chavez to the presidency of Venezuela in 1998 inaugurating with it the Pink Tide of progressive and radical governments in the region. Pink Tide governments undertook a steady reversal of neoliberalism that included the nationalization of natural resources, poverty eradication, economic growth, social inclusion, redistribution of income, and much more. Simultaneously, most of the region began to orient itself commercially toward Asia, especially China, in a mutually beneficial relationship that through growing trade and investment links brought the two sides closer together in an unprecedented development for a region that had hitherto been firmly under the economic and political hegemony of the United States. Thus, political developments and economic trends seemed to guarantee the inexorable emergence of a new world geopolitical architecture within which Latin America would drastically rearrange its institutional and structural links with the United States, bringing about what many Latin American political leaders proclaim as the region's "second economic independence." The growing trade, commercial, and political links between Latin America and China, especially the incorporation of Brazil to the BRICS (Brazil, Russia, India, China, and South Africa), inaugurated the rise of new institutional, political, trade, and commercial structures leading the region to seek to link its economic development to the ever expanding economic weight of the Asiatic giant. Though these highly positive developments have not quite come to a halt, they have been substantially complicated by the negative impact of the world economic crisis since 2008 and the US-led conservative, neoliberal political offensive that has already taken its toll in the victory of Macri in Argentina, the impeachment process against Dilma Rousseff and the installation of the hard-line neoliberal interim government of Michel Temer in Brazil, and the severe economic difficulties faced by Bolivarian government of Nicolas Maduro in Venezuela, just to mention the most important ones. This article seeks to examine the huge potential of Latin America's growing relations with China.